Modeling Physiology of Crop Development, Growth and Yield - Soltani, Afshin; Sinclair, Thomas R.; Ebooks Corporation (Wallingford : CABI, 2012)
Model studies focus experimental investigations to improve our understanding and performance of systems. Concentrating on crop modelling, this book provides an introduction to the concepts of crop development, growth, and yield, with step-by-step outlines to each topic, suggested exercises and simple equations. A valuable text for students and researchers of crop development alike, this book is written in five parts that allow the reader to develop a solid foundation and coverage of production models including water- and nitrogen-limited systems.
Contenido: Crop Management ApplicationsEducational Applications; Exercise; 5 Status of Crop Modeling; Infancy; Juvenility; Adolescence; Maturity; The Future of Crop Modeling; Exercise; Part II: Potential Production Models; 6 Phenology {80}{93} Temperature; Background; Basics; Parameter Estimation; Programming; Additional Notes; Exercises
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CULTIVOS -- DESARROLLO; CULTIVOS -- FISIOLOGIA